Effect of TENS on stimulation of saliva in postmenopausal women with or without oral dryness - An interventional study - Aravinda Konidena; Dheeraj Sharma; Gagan Puri; Avani Dixit; Deepa Jatti; Rajesh Gupta (Elsevier, 2016)
Background: Decreased estrogen levels in postmenopausal women may cause an increase in oral symptoms including dry mouth, burning sensation of the mouth, and taste alterations. Management of salivary gland hypofunction by various modalities had been tried with variable results and associated side effects or discomfort. Aim: To evaluate the effects of transcutaneous electric nerve stimulation (TENS) on whole salivary flow rate in postmenopausal females with and without oral dryness. Methods: Fifty postmenopausal women, based on their response to Xerostomia Inventory, were divided into 2 groups of 25 each; group 1 were postmenopausal women with oral dryness (PMD + OD) and group 2 were postmenopausal women without oral dryness (PMD − OD). Unstimulated whole saliva collection was done by low forced spitting method. External salivary stimulation of parotid gland by electrodes of TENS unit was done and sialometry was repeated. The salivary flow rates were compared within both groups before and after stimulation and between the two groups. Results: The mean salivary flow rates at baseline were statistically significantly lower in the PMD + OD group than the PMD − OD group. There was a mean increase of 0.33 ml and 0.46 ml with TENS stimulation in PMD + OD and PMD − OD groups, respectively. Conclusion: Postmenopausal women with perception of oral dryness had lower salivary flow rates. 90% of the subjects, irrespective of oral dryness status, responded to TENS therapy. TENS stimulation resulted in a statistically significant increase in the quantity of whole saliva flow rate in postmenopausal women with or without oral dryness.